2017
DOI: 10.4269/ajtmh.16-0632
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Brucellosis among Patients Attending a District Hospital in Rwanda

Abstract: Studies on human brucellosis in Rwanda are scarce, and the incidence is likely to be higher than official estimates. In a recent study using Rose Bengal Test (RBT) on women who had aborted or had still births in Huye district, 25% were seroprevalent. Thus, purpose of the present study was to investigate the seroprevalence in patients presenting with the key signs and symptoms of brucellosis. Cross-sectional study was done in Nyagatare District in the Eastern Province of Rwanda. A total of 198 patients were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Yet another study has confirmed seroprevalence of bovine brucellosis of 2.3% in Kigali City (Manishimwe et al 2015). A very recent study at Nyagatare Hospital reported 6.1% seroprevalence of brucellosis in humans (Gafirita et al 2017), confirming that the disease is endemic in the area. In order to effectively control brucellosis, there is an urgent need to develop and implement eradication programmes in view of the risk factors for this disease identified in this study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Yet another study has confirmed seroprevalence of bovine brucellosis of 2.3% in Kigali City (Manishimwe et al 2015). A very recent study at Nyagatare Hospital reported 6.1% seroprevalence of brucellosis in humans (Gafirita et al 2017), confirming that the disease is endemic in the area. In order to effectively control brucellosis, there is an urgent need to develop and implement eradication programmes in view of the risk factors for this disease identified in this study.…”
Section: Discussionmentioning
confidence: 81%
“…The bacteriological and serological evidence as well as epidemiological characteristics of brucellosis in sub-Saharan Africa have been recently reviewed (Ducrotoy et al 2017). There are few publications on bovine brucellosis (Chatikobo et al 2009; Manishimwe et al 2015; Rujeni & Mbanzamihigo 2014) and even fewer on the epidemiology of brucellosis in humans (Gafirita et al 2017; Rujeni & Mbanzamihigo 2014) in Rwanda.…”
Section: Introductionmentioning
confidence: 99%
“…In Rwanda, there are few published studies on bovine brucellosis, and individual animal seroprevalence has been found to range from 2.2% in peri-urban areas of Kigali city to 18.9% in the Nyagatare district [ 14 , 15 , 16 , 17 ]. The seroprevalence of brucellosis in women with a history of abortion was found to be 6.1% at the Nyagatare district hospital [ 18 ] and 25.0% at Huye teaching hospital [ 19 ]. Despite the efforts to control brucellosis in Rwanda, the factors responsible for its persistence remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Rwanda is the smallest country in EAC located at the West of the regional block (Figure 1) and sharing borders with Uganda at the Brucellosis studies have been conducted in Rwanda, although few and scattered over the years (Akayezu, 1984;Chatikoba et al, 2008;Gafirita et al, 2017;Manishimwe et al, 2015;Ndazigaruye et al, 2018;Rujeni & Mbanzamihigo, 2014;Thienpont et al, 1961). In the last decade (2010-2019), a total of four studies were published on animal and human brucellosis in the country (Table 2).…”
Section: Brucellosis Prevalence In Rwandamentioning
confidence: 99%